A Moving Conversation: A Curricular Pathway from Private Dance Studio to Dance in Higher Education. Issue 3 (3rd July 2021) - Gerchman, Robin M.
Abstract: Dance education in the private studio provides multiple perspectives and experiences for understanding dance as a discipline of study. Based on personal experience with a program that I piloted, I share how a private dance studio can provide a pathway to a college liberal arts program through shared synergy. By offering classes that provide a specific foundation for dance course work in higher education, the private studio can ease the transition and support success for students who move on to study dance in college. During the implementation of this program in 2001, I was offered a full-time college teaching position. Although this program did not extend beyond the pilot, this curriculum has continued validity as a model today.